"Conquering the 'Tyrranical Commander:'" Richard Baxter on the Perils of Pride in Christian Ministry. Issue 1 (May 2016) - Setran, David
Pride continues to be a prevalent vice among those who serve as professional ministers and Christian leaders. English Puritan Richard Baxter (1615–1691) was attentive to this concern and wrote a great deal on ministerial pride in his various publications. He explored the ways in which pride infected ministers both through an elevated personal assessment and through a heightened desire for human praise. This article examines his diagnosis of the diverse manifestations of ministerial pride and looks carefully at his recommendations for addressing its corrosive influence, providing insights and suggestions for contemporary Christian ministers.